Funeral in blue - Perry, Anne. (New York : Ballantine Books, 2001)
When two women are found strangled in the studio of a London artist, including the wife of Dr. Kristian Beck, who is accused of the killing, William Monk, his wife Hester, and their close friend, Lady Callandra Daviot, set out to clear their friend's name.
Keywords: Monk, William (Fictitious character) -- Fiction; Private investigators -- England -- London -- Fiction; Nurses -- Fiction; London (England) -- Fiction; Historical fiction; Mystery fiction